2006
DOI: 10.2166/ws.2006.765
|View full text |Cite
|
Sign up to set email alerts
|

Influence of calcium-NOM complexes on fouling of nanofiltration membranes in drinking water production

Abstract: The application of nanofiltration is growing rapidly in drinking water and wastewater treatment. The main problem during the operation of nanofiltration membranes is membrane fouling, part of which is due to the presence of Natural Organic Matter (NOM) in sources for drinking water. In this work the effect of calcium was investigated on the nanofiltration fouling behavior in relation to NOM. From Li and Elimelech (2004) it is known that calcium enhanced membrane fouling significantly due to the formation of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…When saline water feed was filtered, the rapid formation of brown deposit on the membrane surface could be observed visually, caused by the aggregation of humic substances due to its interactions with salt ions in seawater. The abundance of salt ions in the feed solution may have also contributed towards aggregation due to the formation of salt-NOM complexes (Cornelissen et al, 2006). Given the high salinity of the feed solution used in this study, the aggregation observed is likely to be more severe compared to other studies utilizing lower salt concentrations.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…When saline water feed was filtered, the rapid formation of brown deposit on the membrane surface could be observed visually, caused by the aggregation of humic substances due to its interactions with salt ions in seawater. The abundance of salt ions in the feed solution may have also contributed towards aggregation due to the formation of salt-NOM complexes (Cornelissen et al, 2006). Given the high salinity of the feed solution used in this study, the aggregation observed is likely to be more severe compared to other studies utilizing lower salt concentrations.…”
mentioning
confidence: 92%
“…Both EPS and humic substances have the potential to cause significant irreversible organic fouling (Baghoth et al, 2008;Katsoufidou et al, 2008Katsoufidou et al, , 2010. Furthermore, a high concentration of divalent salts present in seawater significantly increases the fouling potential of organic matter (Cornelissen et al, 2006). Better understanding of the mechanisms involved may lead to more effective fouling mitigation methods.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, divalent ions of seawater could significantly increase the fouling by the organic matter [36]. Therefore, several types of ions are added to the synthetic seawater.…”
Section: Introductionmentioning
confidence: 99%
“…Including extra measurements such as total organic carbon and the concentration of individual ions in the feed water, can give more detailed data about these different types of fouling, and would thus further improve the predictive power of the data-driven model. For example, data on organic carbon (the quality of which was found to be insufficient here) is known to enhance fouling by forming complexes with calcium, and could have supplemented the calcium data (which was collected further in the distribution network) [53]. Nevertheless, lumping the different fouling dynamics in the online measured conductivity and the offline measured calcium concentration seems to be sufficient in practice here.…”
Section: Data-driven Fouling Modelsmentioning
confidence: 99%